Regional planning is dead: long live planning regional futures. Issue 1 (2nd January 2021) - Harrison, John; Galland, Daniel; Tewdwr-Jones, Mark
ABSTRACT: This paper starts from the premise that regional planning as it is known is now defunct and something that we need to get used to. Identifying those disruptive elements that have undermined traditional forms of institutionalized regional planning, it is argued that contemporary planning debates are too obsessed with the institutional planning frame and have become distracted from the changing content of the real-world picture. The aim in this paper is to reassert the purpose and values of planning by rediscovering the content, conceptualize multiple and fluid forms of planning frames, and reposition the planner as an orchestrator and enabler of planning regional futures.